Food avoidance taboos and maternal diets in Myanmar - Linn, Khin Mar; Headey, Derek D.; Masias, Ian (International Food Policy Research Institute, 2024)
Presentation given December 11, 2024 for Food Avoidance Taboos and Maternal Diets Learning Module Presentation.